Nursing practice - Reality or dream - C. Searle (AOSIS, 1984)
For the purpose of this article, the term nursing practice excludes midwifery practice. The debate as to whether a nurse is a practitioner or not centres on the nurse and not on the midwife. Both legally and by customary practice, the midwife in South Africa has enjoyed the status of a practitioner since 1652, whilst the nurse has only been recognised as a legal practitioner since 1891.